Pengaruh Perbandingan Massa Tanah dan Pupuk Kandang Ayam terhadap Pertumbuhan dan Hasil Tanaman Buncis Tegak (Phaseolus vulgaris L.) - Rini Sitawati; Firman Satya Nugraha; Fiqriah Hanum Khumairah; Sri Nur Widyastuti L (Paspalum: Jurnal Ilmiah Pertanian, 2021)
Common bean (Phaseolus vulgaris L) is one type of vegetable crop favored by the Indonesian people. Its  cultivation requires specific planting medium and rich in nutriens to meet plant growth and development need. This study aims to obtain the best ratio of soil mass and chicken manure fertilizer which can increase common bean growth and yield . This experiment was conducted from April 2019 to June 2019, in Langensari Village, Lembang District, West Bandung Regency with an altitude of 1,200 m above sea level. The experiment used  Randomized Block Design (RBD)consisted of 5 treatments and repeated 5 times, namely  A = 4.0 kg of soil: 0.0 kg chicken manure , B = 2.0 kg of soil: 2.0 kg chicken manure , C =1,3 kg of soil  :2,7  kg chicken manure, D= 1,0 kg of soil : 3,0 kg chicken manure, and E = 2,7 kg of soil : 1,3 kg chiken manure per polibag.  Results showed that the use of planting media with a soil media mass ratio of  2,0 kg of soil : 2,0 kg chiken manure increase  plant height, number of leaves, number of fruits, fruit length and fruit weight compared the other treatmens, but the  flowering and fruiting age of the plants were not different beetwen  between treatments given.